The impact of school content on the motivation for motor skills performance among secondary school students: A field study at Martyr Marzouk Dahman High Schoo - Messaoudi, saleh; khalfouni, mohemed adnane (sports creativity, 2025)
This study aims to find out the extent of the impact of the taught content on the motivation of the motor skill performance of high school students and the content of physical education and sports. 20 pupils practicing physical and athletic activity and 20 pupils exempt from the physical education and sports class and this is to conduct the basic study, and we used a measure of motivation performance on practicing pupils and non-practitioners in physical and athletic activity in light of the content taught by high school students, and at the conclusion of this study we found that the effectiveness And the role of the taught content has a great impact on the motivation of the motor skill performance of secondary school students